Alcohol consumption in adolescents - Ilona Plevová; Michaela Hlávková (University of Ostrava, 2016)
Aim: To determine the level of alcohol consumption in a selected group of adolescents. Design: A descriptive cross-sectional study. Methods: The data were obtained using a part of the standardized ESPAD questionnaire for assessing consumption of alcoholic beverages. The sample comprised 422 students from seven secondary schools of different types in the city of Ostrava. For statistical analysis, the chi-squared test and Fisher's exact test (for n ≤ 5) were used. The data were processed using Stata v. 10. Results: More than half of respondents first tried alcohol before the age of 15. The most frequent alcohol-related problems were unprotected sex, decreased school performance and problems with parents or friends. Incomplete families were found to be an important factor in adolescents preferring and more frequently drinking beer. Conclusion: The study confirmed results reported by the Europe-wide survey ESPAD, namely that adolescents start to drink alcohol as early as before they turn fifteen.